2007
DOI: 10.1038/nature05953
|View full text |Cite|
|
Sign up to set email alerts
|

Non-transcriptional control of DNA replication by c-Myc

Abstract: The c-Myc proto-oncogene encodes a transcription factor that is essential for cell growth and proliferation and is broadly implicated in tumorigenesis. However, the biological functions required by c-Myc to induce oncogenesis remain elusive. Here we show that c-Myc has a direct role in the control of DNA replication. c-Myc interacts with the pre-replicative complex and localizes to early sites of DNA synthesis. Depletion of c-Myc from mammalian (human and mouse) cells as well as from Xenopus cell-free extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
551
3
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 585 publications
(589 citation statements)
references
References 49 publications
33
551
3
2
Order By: Relevance
“…The molecular mechanism(s), however, by which transcription factors increase origin selectivity are still largely unknown (34). Transcription factors can also play crucial roles in origin activation, such as the c-Myc proto-oncogene, whose overexpression causes an increase in the number of active replicons (15). Since the origins examined in our study were all bound by pre-RC factors in the cells analyzed, independently of exogenous HOXD13 gene expression (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism(s), however, by which transcription factors increase origin selectivity are still largely unknown (34). Transcription factors can also play crucial roles in origin activation, such as the c-Myc proto-oncogene, whose overexpression causes an increase in the number of active replicons (15). Since the origins examined in our study were all bound by pre-RC factors in the cells analyzed, independently of exogenous HOXD13 gene expression (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cdt1 has been shown to physically interact with Cdc6 in several organisms. In addition, a recent paper reported that human Orc6 co-immunoprecipitates with Cdt1 (34). In theory, geminin could disrupt either of these interactions (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, most of its targets are only moderately affected by Myc (reviewed by Dang et al, 2006). In addition, Myc has transcription-independent roles in the control of DNA replication (Dominguez-Sola et al, 2007).…”
Section: Introductionmentioning
confidence: 99%